Use of Nanotechnological Building Materials in the Turkish Construction Industry - Yeliz Tülübaş Gökuç (Journal of Sustainable Construction Materials and Technologies, 2019)
The competitiveness of firms in the construction industry can be said to lie on technological developments. Owing to new technologies it is possible to reduce costs and respond to varying customer demands. Nanotechnology affects many sectors as a technology that contributes significantly to the development of the features of materials, and there are many applications in the construction industry as well as in many other areas. Research and development studies have shown that nanotechnology can improve the performance of traditional building materials such as concrete and steel. The construction industry is the major contributor to the environmental problems with the construction, operation and maintenance of buildings. The potential contribution to sustainability is to make the nanotechnology one of the most influential technologies in green buildings. Although nanotechnological materials are ready to be widely used in the construction industry, they have not had an important effect on the sector, yet. The purpose of this study is to better understand the adaptation of nanotechnology in the context of the Turkish Construction Industry, and to evaluate the current applications in nanotechnology. A survey was designed to capture the required data for this study